Algorithms for managing patients with structural heart abnormalities in therapeutic practice - E. A. Barabanova; A. A. Arakelyants; T. V. Zaugolnikova; T. E. Morozova (Лечащий Врач)
Among structural heart abnormalities (SНA) in clinical practice, mitral valve prolapse, an open oval window, and atrial septal aneurysm, which can present a real threat to the health and life of patients, are most common. Frequent subclinical course makes it difficult to detect them in a timely manner and requires focused attention of practicing doctors in assessing the phenotypic features of the structure of the musculoskeletal system and connective tissue, which can serve as markers of latent defects in the development of the heart. The article provides data on the most typical symptoms and clinical manifestations of SНA, possible complications and therapeutic tactics. Early detection of structural abnormalities of the heart and the choice of the right tactics for passive or active monitoring of patients with varying degrees of severity of defects in the development of the heart will help preserve the health or even life of patients.